2021
DOI: 10.20396/bjos.v20i00.8663400
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and behavioral conditions in oral health of volleyball and soccer athletes

Abstract: Aim: In this cross-sectional study, we evaluated the oral hygiene habits, oral health conditions, and the perception about the influence of oral health conditions on the physical performance of youth and professional volleyball and soccer athletes. Methods: A total of 96 male athletes participated: 48 volleyball players (25 youth and 23 professional players); and 48 soccer players, of whom 22 were youth, and 26 were professional players. We analyzed the oral hygiene and oral health condition (daily toothbrush,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…A recent study reported that occlusal disturbances negatively influenced athletic performance, where there were increases in athletes with asymmetric muscle contractions ( p = 0.025) coupled with decreased muscle power ( p = 0.030) [ 18 ]. A significant influence of dental/facial trauma on physical performance ( p = 0.006) in young professional volleyball and soccer athletes has also been reported [ 66 ]. Malocclusion and its treatments can influence body posture, foot–ground contact, center of mass, footprint, etc.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that occlusal disturbances negatively influenced athletic performance, where there were increases in athletes with asymmetric muscle contractions ( p = 0.025) coupled with decreased muscle power ( p = 0.030) [ 18 ]. A significant influence of dental/facial trauma on physical performance ( p = 0.006) in young professional volleyball and soccer athletes has also been reported [ 66 ]. Malocclusion and its treatments can influence body posture, foot–ground contact, center of mass, footprint, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Avaliou-se o histórico de trauma orofacial em praticantes de Vôleibol, onde 12,5% desses relataram histórico positivo para a ocorrência desse tipo de trauma (Souza et al, 2021). Em relação aos entrevistados da presente pesquisa, 46,3% indicariam o uso para a prática do vôlei.…”
Section: Discussionunclassified